Advances in mergers and acquisitions. Vol. 19 - Finkelstein, Sydney; Cooper, Cary L. (Emerald Publishing Limited, 2020)
Advances in Mergers and Acquisitions stands out from the competition due to its focus on three key characteristics: studies from scholars in different countries, with different research questions, relying on different theoretical perspective. Such a broad and inclusive approach to mergers and acquisitions is not easily replicated in academic journals, with much narrower mandates and metrics. The chapters published in this volume provide cutting edge ideas by leading scholars and help to inform mergers and acquisitions research around the world. Volume 19 of this annual series explores a range of issues that include: mergers waves, roll-up acquisitions, hostile takeovers, M&A experience, and decision-making, corporate governance, and innovation in mergers and acquisitions. This book is of interest to scholars in strategic management, organization theory, and organizational behaviour who are studying questions around mergers and acquisitions. Doctoral students in particular will benefit from access to the diversity of research that can trigger new research questions and expanded research agendas.
Includes index.
Keywords: Consolidation and merger of corporations.; Business & Economics -- Mergers & Acquisitions.; Corporate finance.; elektronické knihy; electronic books